Reciprocal development in vocabulary and reading skills - Ricketts, J (2009)
Data are presented in seven chapters that address the reciprocal relationship between oral vocabulary and reading development. Chapter 2 explores exception word reading in poor comprehenders longitudinally, finding deficits that are pervasive over a period of two years. The results support the hypothesis that weak oral vocabulary skills are causally related to poor exception word reading in this group. In Chapter 3, orthographic and semantic skills in poor comprehenders are investigated in a word learning paradigm. This chapter provides evidence that poor comprehenders have more difficulty learning and retaining semantic information than orthographic information. A similar paradigm is described in Chapter 4 to investigate predictors of orthographic and semantic learning. In a large group of typically developing readers, this demonstrates that decoding is the strongest predictor of orthographic learning while existing oral vocabulary knowledge is the strongest predictor of semantic learning. In Chapters 5 and 6 orthographic and semantic skills in poor comprehenders and children with dyslexia are compared using standard off-line tasks (Chapter 5) and an online word learning experiment (Chapter 6). These chapters indicate similarities as well as differences in the reading and language profiles of these groups. Chapter 7 adopts a different approach by using a word learning study to investigate the benefit of teaching new oral vocabulary in the presence of orthography.